Perfil nutricional de híbridos de milho geneticamente modificado e o seu isogênico convencional - Amaral, Camila Carvalho dos Santos (2016)
The objective of this work was to confirm that genetically modified corn (GM) presented in this study have composition substantially equivalent to their nonGM isogenic hybrid, unless when considering characteristics introduced to them. Five GM hybrids were evaluated, Maximus Bt11, MIR162, GA21, Bt11xGA21 and Bt11xGA21xMIR162, as well as conventional Maximus, a conventional hybrid isogenic to the GM hybrids. The experiments were conducted in a randomized blocks design, with three replicates, in two locations in the state of Minas Gerais, Brazil, the municipalities of Uberlêndia and Ituiutaba, during harvest 2008/2009. The characters related to forage and grain composition, as well as mineral components, fatty acids and amino acids in the grain, were evaluated. The data of each GM hybrid and of the conventional hybrid were compared, analyzing the significance with the F test at 5% of probability. The average levels of each nutritional component were also compared with the compositional databank for corn culture, maintained by the International Life Sciences Institute (ILSI, 2010). We verified that no consistent pattern emerged to suggest significant biological changes in the composition or nutritional value of the grain and forage of GM corn hybrids Bt11, MIR162, GA21, Bt11xGA21 and Bt11xMIR162xGA21. The levels of the evaluated components were, mostly, within the amplitudes related to corn, according to the databank for corn culture of the ILSI (2010). This demonstrates that the nutritional composition of GM corn hybrids here reported are substantially equivalent to their respective conventional isogenic hybrid.